eHealth usage among Chinese college students: qualitative findings - Hua-xuan LIU; Bik-chu CHOW; Chun HU; Holger HASSEL; Wendy Yajun HUANG (BMC, 2022)
Abstract Background The information technology has developed rapidly with the evolution of internet environment transformed from requiring computer skills for information searching to self-managing health data and applying information. Therefore, a more diverse range of eHealth skills is required and these skills are referred as eHealth literacy. However, most eHealth literacy studies focused mainly on information searching skills. Little is known about eHealth usage behaviors of college students in this day and age. Objectives This study aimed to investigate how Chinese college students engage with eHealth tools and to determine the elements of their eHealth literacy. Methods A purposive sample of 18 Chinese college students was recruited for in-depth interviews. Interviewees included three males and three females of each city (Beijing, Wuhan and Putian) from sports, medical, and non-health-related majors. Conventional content analysis was applied for data analysis. Results The eHealth usage of different-major-students were compared and profiled by three themes of Expectance, Usage pattern and Perception. In Expectances, non-health major students applied eHealth only for urgent health need, sport major students used it to monitor health while medical major students, as frequent users for searching health database. In Usage pattern, purposes of eHealth for personal, practical and theoretical were identified for non-health major, sport major and medical major groups, respectively. In Perceptions, sport students felt more curious about eHealth than the other groups who perceived either fear (non-health students) or skeptical (medical students). By compiling those themes, the whole picture of eHealth usage was emerged. Based on that, the current study identified the related skills using the trilogy of Web 1.0 to 3.0, and derived a conceptual framework for eHealth literacy in the present day. Conclusions The current study obtained a comprehensive understanding of eHealth usage and a framework of eHealth literacy required for Chinese college students. And it gives a clearer look at web 3.0 related eHealth behaviors.